Divine Tobacco: A Paradox Among Health Fascism - Hendra Herman; Hardian Satria Jati; Susila Susila; Wempy Setyabudi Hernowo; M. Aufar Saputra Pratama Erawan (Institut Teknologi Sepuluh Nopember, 2021)
One way of conventional medicine in Indonesia is the herbal medicinal plant tobacco which is a controversial plant. However, currently, many types of businesses offer health services using alternative medicine using traditional medicine. Of course, this is contrary to the anti-tobacco campaign launched by the government and the regulations on tobacco contained in various laws and regulations. Therefore, this study aims to examine how the legal system regarding tobacco is related to conflicts of interest in tobacco use for treatment. This research is normative juridical research. Through a statutory and conceptual approach, the aim is to understand the importance of using tobacco as alternative medicine. The results of this study are that the government should make tobacco a priority for traditional medicine media and provide legality to community therapy houses because it is proven that tobacco can make a positive contribution to improving health.